Effectiveness of Lemongrass (Cymbopogon citratus) Decoction as a Non-Hormonal Therapy for Preventing Early Menopause Among Women Aged 40–45 Years in Indonesia: A Randomized Controlled Trial - Sembiring, Mediana Beru; Simamora, Lasria; Hutabarat, Dewi Sartika; Panjaitan, Polma Ria Metawati; Tarigan, Imarina; Nisa, Rika Khairatun; Arjuna, Ratu Putri (Chakra Brahmanda Lentera Institute, 2025)
Background: Early menopause (before age 45) increases risks of osteoporosis, cardiovascular disease, and reduced quality of life. Although hormonal therapy is effective, its adverse effects have driven interest in safer alternatives. However, evidence on community-based herbal interventions for preventing early menopause is scarce in Indonesia. This study examined the effectiveness of Cymbopogon citratus (lemongrass) decoction as a low-cost, non-hormonal preventive therapy for early menopause. Methods: This parallel two-arm randomized controlled trial, conducted in Perbulan Village, Karo Regency, involved 30 women aged 40–45 years, randomly assigned to an intervention group receiving lemongrass decoction and a control group. Participants consumed 250 ml of decoction daily for 30 days. Menopausal symptoms were measured using the Menopause Rating Scale (MRS) and menstrual cycle regularity was recorded. Data were analyzed with the Mann–Whitney U test following the CONSORT 2010 guidelines, with statistical significance set at p < 0.05 and 95% confidence intervals (CI) reported. Ethical approval was obtained from the institutional review board. Results: Mean MRS scores in the intervention group decreased significantly from 20.5 ± 2.0 to 13.4 ± 1.6 (p < 0.001, 95% CI [5.7, 8.4], d = 1.45, large effect), while the control group showed no significant change. Menstrual cycle regularity improved in 73.3% of intervention participants compared with 13.3% in controls (p < 0.001). Compliance was high (86.7%) and no adverse events were reported. Conclusion: Lemongrass decoction effectively reduced menopausal symptoms and regulated menstrual cycles, supporting its use as a safe, acceptable, and affordable non-hormonal option for community-based women’s health promotion. The findings suggest potential integration of herbal therapy education into midwifery and public health programs to strengthen preventive reproductive care.